Pipe flow : a practical and comprehensive guide - Rennels, Donald C., 1937- (John Wiley & Sons, Inc., 2022)
"With its detailed coverage of pressure drop and other phenomena related to fluid flow in piping systems this book enables readers to design and analyze piping systems needed to support a broad range of industrial operations, distribution systems, and power plants. Throughout the book, accurate prediction and management of pressure loss while working with a variety of piping components and piping systems is demonstrated. The book draws together and reviews the growing body of experimental and theoretical research on fluid flow in piping and its components, including important loss coefficient data. The results are presented in straight forward tables and diagrams, as well as in broadly applicable equations. Sample problems and their solutions are provided throughout the book, demonstrating how core concepts are applied in practice. In addition, references and further reading sections enable the reader to explore all topics in greater depth. The book employs two systems of units: the English gravitational system and the International System. Pipe Flow, Second Edition contains additional information to broaden understanding and management of fluid flow in piping systems. Many sections of the book have been refined and augmented and new material has been added including a chapter, The Liquid Jet Pump, that presents a mixing section flow model that can be used to accurately predict jet pump performance. A new appendix section on Speed of Sound in Water and numerous new examples have been added."--